Assessment on the efficacy of Parkia speciosa hassk. pericarps methanol extract as a potential antimicrobial agent / Raihan Zafirah Affendi - Affendi, Raihan Zafirah (2016)
The persistent development of resistant strains of bacteria which resulted in a condition known as antibiotic resistance is an alarming situation. Therefore, the need for development of novel antimicrobial agent such as by using herbal medicine is in great demand. Parkia speciosa Hassk.(P. speciosa Hassk.), known as bitter beans, is commonly eaten among Malaysian and known to have medicinal properties. The present study was conducted to evaluate the potential of methanol extract of pericarp from P. speciosa as an antimicrobial agent. Thus, the extract of pericarp of P. speciosa Hassk. prepared using methanol as an extraction solvent were screened for its antimicrobial activities and phytochemical composition. The pericarps were left to dry and transformed into powder form before being soaked in methanol for about 24 days using the exhaustive extraction method. The extract was tested against food poisoning causative agents which were Staphylococcus aureus, Bacillus cereus, Salmonella typhimurium and Escherichia coli. The antimicrobial activities were evaluated by using the technique of agar diffusion and broth microdilution method. Both techniques were used to screen antimicrobial susceptibility (AST), minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) at concentrations of 1000,500,250, 125,62.5,31.25, 15.62,7.81,3.90, 1.90 and 0.9 mg/ml. Best inhibitory effects were shown against S. aureus and B. cereus compared to S. typhimurium and E. coli which showed no inhibitory effects. The MIC and MBC of the methanol extract P. speciosa Hassk. pericarp against S. aureus was found to be 7.8 mg/ml while MIC and MBC of B. cereus were quite impressive which was found to be 1.9 mg/ml. Phytochemical analysis revealed presence of alkaloids, carbohydrates, flavonoids, tannins and amino acid. The study managed to prove that methanol extract of P. speciosa pericarp has potential to be used as an antimicrobial agent. The preliminary testing on antimicrobial activity conducted clearly revealed that S. aureus and B. cereus were more susceptible compared to S. typhimurium and E. coli. The medicinal activities may be attributed by the existence of one or more of the detected phytochemical compounds within the extract.